The first experience of successful pregnancy after simultaneous liver-kidney transplantation with reno-portal transposition - O. V. Tkachenko; K. U. Vilchuk; O. O. Rummo; I. V. Kurlovich; A. E. Shcherba; I. V. Naumchik; C. Yu. Nagibovich; O. A. Pankratova; V. V. Rimashevski; M. V. Beluga; D. A. Fedoruk (Вестник трансплантологии и искусственных органов)
The article is dedicated to the problem of pregnancy management and delivery after simultaneous liver-kidney transplantation (SLKT). The article contains general historic and statistic information, and presents the first real world clinical case of favorable pregnancy outcome in patient after simultaneous liver-kidney transplantation with reno-portal transposition.